Gastric volvulus and associated gastro-oesophageal reflux. Issue 5 (November 1995) - Samuel, M; Burge, D M; Griffiths, D M
Abstract : Between 1984 and 1994, 10 neurologically normal children between 2 and 24 months were diagnosed as having gastric volvulus with associated gastro-oesophageal reflux (GOR). The common features at presentation were episodic colicky abdominal pain, non-bilious vomiting, upper abdominal distension, haematemesis, and failure to thrive. Anterior gastropexy and conservative management of GOR was curative.